Proceedings of the Fourteenth ACM Conference on Electronic Commerce 2013
DOI: 10.1145/2482540.2482612
|View full text |Cite
|
Sign up to set email alerts
|

Revenue optimization in the generalized second-price auction

Abstract: We consider the optimization of revenue in advertising auctions based on the generalized second-price (GSP) paradigm, which has become a de facto standard. We examine several different GSP variants (including squashing and different types of reserve prices), and consider how to set their parameters optimally. One intriguing finding is that charging each advertiser the same per-click reserve price ("unweighted reserve prices") yields dramatically more revenue than the quality-weighted reserve prices that have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 19 publications
(24 reference statements)
0
8
1
Order By: Relevance
“…We now investigate such ad-limited auctions, making the simplifying assumption that all J auctions are single item auctions. In contrast to previous work which has suggested that a per-impression reserve is a poor tool for increasing revenue or trading-off between revenue and other objectives [Roberts et al 2013;Thompson and Leyton-Brown 2013], this analysis shows that the use of such a reserve is the optimal way of controlling the number of ads shown. THEOREM 4.6.…”
Section: Constrained Optimizationcontrasting
confidence: 94%
See 3 more Smart Citations
“…We now investigate such ad-limited auctions, making the simplifying assumption that all J auctions are single item auctions. In contrast to previous work which has suggested that a per-impression reserve is a poor tool for increasing revenue or trading-off between revenue and other objectives [Roberts et al 2013;Thompson and Leyton-Brown 2013], this analysis shows that the use of such a reserve is the optimal way of controlling the number of ads shown. THEOREM 4.6.…”
Section: Constrained Optimizationcontrasting
confidence: 94%
“…Nevertheless, Theorem 3.1 can at the very least be applied to optimizing linear approximation of the φ i . Thompson and Leyton-Brown [2013] observed that φ i is in fact linear for uniform value distributions. In fact, many Beta distributions are also close to linear for much of their range.…”
Section: Implications For Gspmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanism design for online advertising has been extensively studied in the literature. Many discussions have been centered around search advertising auctions, such as the generalized first-price auction (Edelman et al, 2007), the generalized second-price auction (Edelman et al, 2007;Lahaie and McAfee, 2011;Lahaie and Pennock, 2007;Varian, 2007), the Vickrey-Clarke-Groves (VCG) auction (Parkes, 2007;Varian, 2009;Varian and Harris, 2014) and the optimal auction (Feldman et al, 2010;Ostrovsky and Schwarz, 2011;Thompson and Leyton-Brown, 2013) which extends Myerson's optimal auction for a single indivisible good (Myerson, 1981). Most of these studies on advertising auctions examine the properties of an auction model with respect to incentive compatibility, expected revenue, individual rationality, and computational complexity.…”
Section: Related Workmentioning
confidence: 99%